2016
DOI: 10.1149/07509.0221ecst
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Band Structure at GaAs/4H-SiC Heterojunctions

Abstract: The effects of thermal annealing process on the interface in p+-GaAs/n-SiC heterojunctions fabricated by using surface-activated bonding (SAB) were investigated. It was found by measuring their current-voltage (I-V) characteristics that the reverse-bias current and the ideality factor were extracted to be 7.57 ´ 10-7 A/cm2 and 1.33, respectively, for the junctions annealed at 400 °C. The flat-band voltage obtained from capacitance-voltage (C-V) measurements was found to be 1.29 eV, which is almost consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Also, SAB enables us to fabricate any heterointerfaces free from structural defects such as dislocations and cracks, even for the bonding of dissimilar materials with different crystal structures and lattice constants, unlike epitaxial growth methods. Recently, SAB is applied to the next-generation semiconductors such as diamond, 2) SiC, [3][4][5][6] and GaN, [7][8][9] as well as to the basic semiconductors such as Si and GaAs, [10][11][12][13] towards low-resistance semiconductor-tosemiconductor hetero-interfaces free from adhesive intermediate layers. Functional devices with hybrid structures, such as high-power semiconductor lasers with a low interface thermal resistance 4) and high-efficiency multi-junction solar cells with a low interface electrical resistance, 14,15) are so far demonstrated with this direct bonding method.…”
Section: Introductionmentioning
confidence: 99%
“…Also, SAB enables us to fabricate any heterointerfaces free from structural defects such as dislocations and cracks, even for the bonding of dissimilar materials with different crystal structures and lattice constants, unlike epitaxial growth methods. Recently, SAB is applied to the next-generation semiconductors such as diamond, 2) SiC, [3][4][5][6] and GaN, [7][8][9] as well as to the basic semiconductors such as Si and GaAs, [10][11][12][13] towards low-resistance semiconductor-tosemiconductor hetero-interfaces free from adhesive intermediate layers. Functional devices with hybrid structures, such as high-power semiconductor lasers with a low interface thermal resistance 4) and high-efficiency multi-junction solar cells with a low interface electrical resistance, 14,15) are so far demonstrated with this direct bonding method.…”
Section: Introductionmentioning
confidence: 99%
“…Wafer bonding technologies 5,9) such as surface activated bonding (SAB) 10) provide a practical solution to overcoming such difficulties. Several authors reported on wafer-bondingbased GaAs=GaN, 11) GaAs=4H-SiC, 12,13) and Si=4H-SiC junctions. [14][15][16][17] We previously fabricated Si=4H-SiC pn and nn junctions by SAB, and found that ≈6-nm-thick amorphous-like layers observed at the as-bonded Si=SiC interfaces were recrystallized and the reverse-bias characteristics as well as the ideality factors were improved when the junctions were annealed at 1000 °C for 60 s in N 2 ambient.…”
Section: Introductionmentioning
confidence: 99%